An Experimental Investigation into the Onset of Smearing Damage in Nonconformal Contacts with Application to Roller Bearings - Fowell,M; Ioannides,S; Kadiric,A (Tribology Transactions, 2014)
The onset of smearing damage was studied under controlled conditions in a custom test rig that simulates the passage of a rolling element through loaded and unloaded zones of a rolling bearing. The setup includes a spherical roller that is intermittently loaded between two bearing raceways driven at a prescribed speed. The roller is free to accelerate during the loading phase. Contact load, roller speed and acceleration, and electrical contact resistance are recorded during the test. Contact shear stress, friction coefficient, frictional power intensity, and elastohydrodynamic film thickness are calculated from the recorded kinematics data. Results suggest that the first onset of smearing occurs early in the loading phase where the roller is near stationary and the frictional power intensity is high. The raceway speed at the onset of damage decreases with increasing load and increasing lubricant supply temperature. The maximum frictional power intensity is found to be relatively constant at all contact conditions that led to smearing. An existing thermomechanical contact model is used to estimate the contact temperature distribution under smearing conditions and the potential for elastohydrodynamic lubrication (EHL) film thickness reduction due to forward heat conduction.